Active material, all-solid-state battery, and method for producing active material

The active material with controlled infrared peak ratios and crystal phases, along with voids and enhanced surface polarity, addresses the volume change issue in silicon-based electrodes, improving durability and energy density in all-solid-state batteries.

JP7613889B2Active Publication Date: 2025-01-15TOYOTA JIDOSHA KK +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020188134
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-11
Publication Date
2025-01-15
Estimated Expiration
2040-11-11

AI Technical Summary

Technical Problem

Silicon-based active materials in all-solid-state batteries experience significant volume changes during charging and discharging, leading to decreased durability and energy density due to the large volume change of the electrode layer.

Method used

An active material is developed with specific infrared peak intensity ratios (I1 and I2) and crystal phases (clathrate type II, type I, and diamond-type Si) to suppress volume changes, incorporating voids within primary particles and enhancing surface polarity to improve affinity with solid electrolytes.

Benefits of technology

The active material effectively reduces volume changes in the electrode layer, maintaining durability and enhancing energy density by uniform dispersion and reaction uniformity, thereby reducing the need for confining pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613889000002
    Figure 0007613889000002
  • Figure 0007613889000003
    Figure 0007613889000003
  • Figure 0007613889000004
    Figure 0007613889000004
Patent Text Reader

Abstract

To provide an active material capable of suppressing a volume change of an electrode layer during charging and discharging.SOLUTION: An active material used for an all-solid-state battery according to the present invention contains at least Si, and in the infrared spectroscopic spectrum, when the maximum peak intensity at 900 cm-1 or more and 950 cm-1 or less is I1, and the maximum peak intensity at 1000 cm-1 or more and 1100 cm-1 or less is I2, the I1 and the I2 satisfy 0.55≤I2 / I1≤1.0 and 0.01≤I1.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an active material, an all-solid-state battery, and a method for producing the active material. [Background technology]

[0002] An all-solid-state battery is a battery having a solid electrolyte layer between a positive electrode layer and a negative electrode layer, and has the advantage that it is easier to simplify safety devices compared to liquid batteries having an electrolyte solution containing a flammable organic solvent. In addition, Si-based active materials are known as active materials used in all-solid-state batteries. For example, Patent Document 1 discloses an anode for a sulfide all-solid-state battery having an anode active material layer containing at least one material selected from the group consisting of Si and Si alloys as an anode active material.

[0003] Patent Document 2 discloses a silicon oxide structure containing, as components, a silicon oxide skeleton containing Si and O in its atomic composition and silicon-based nanoparticles chemically bonded to the silicon oxide skeleton. Furthermore, Patent Document 2 discloses a silicon oxide structure containing, as components, a silicon oxide skeleton containing Si and O in its atomic composition and silicon-based nanoparticles chemically bonded to the silicon oxide skeleton. -1 The intensity of peak 1 due to the Si-H bond in 1 ) and 1000~1200cm -1 Peaks due to Si-O-Si bonds in 2 Intensity (I 2 ) ratio (I 1 / I 2 ) is within a specified range.

[0004] In addition, Patent Document 3 describes a spectrum measured by an infrared spectrometer, in which the peak at 3400 to 3800 cm -1 Peak A originating from silanol groups in 1 Strength and 1000~1200cm -1 Peak A originating from siloxane bonds 2 The intensity ratio value A 1 / A 2 SiO x (Negative electrode active material for lithium ion secondary batteries) is disclosed.

[0005] Patent Document 4 discloses a method for producing a 600 cm infrared spectroscopy image sensor comprising base particles made of silicon oxide and a coating layer made of a conductive carbon material that covers at least a part of the surface of the base particles. -1 ~1400cm -1 900cm when the maximum peak intensity of the infrared absorption spectrum of -1 A negative electrode active material having a strength of 0.30 or more at 1000 V is disclosed. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-142431 A [Patent Document 2] JP 2019-119638 A [Patent Document 3] JP 2011-108635 A [Patent Document 4] International Publication No. 2014 / 119238 Summary of the Invention [Problem to be solved by the invention]

[0007] Si has a large theoretical capacity and is effective for increasing the energy density of a battery. On the other hand, Si has a large volume change during charging and discharging. Therefore, an electrode layer using Si has a large volume change during charging and discharging. The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide an active material capable of suppressing the volume change of an electrode layer during charging and discharging. [Means for solving the problem]

[0008] The present disclosure provides an active material for use in an all-solid-state battery, which contains at least Si and has an infrared spectrum of 900 cm -1 More than 950cm -1 The maximum peak intensity at I 1 and 1000 cm-1 More than 1100cm -1 The maximum peak intensity at I 2 In this case, the above I 1 and I above 2 However, 0.55≦I 2 / I 1 ≦1.0 and 0.01≦I 1 To provide an active material that satisfies the above requirements.

[0009] According to this disclosure, I 2 / I 1 The value of is within a given range, and I 1 Since the value of is also within a predetermined range, it is possible to obtain an active material capable of suppressing the volume change of the electrode layer during charging and discharging.

[0010] In the above disclosure, 1 However, 0.02≦I 1 ≦0.08 may be satisfied.

[0011] In addition, the present disclosure provides an active material for use in an all-solid-state battery, which contains at least Si and has an infrared spectrum of 900 cm -1 More than 950cm -1 The maximum peak intensity at I 1 and 1000 cm -1 More than 1100cm -1 The maximum peak intensity at I 2 In this case, the above I 1 and I above 2 However, 0.55≦I 2 / I 1 ≦1.0 and 0.01≦I 2 To provide an active material that satisfies the above requirements.

[0012] According to this disclosure, I 2 / I 1 The value of is within a given range, and I 2 Since the value of is also within a predetermined range, it is possible to obtain an active material capable of suppressing the volume change of the electrode layer during charging and discharging.

[0013] In the above disclosure,2 However, 0.02≦I 2 ≦0.08 may be satisfied.

[0014] In the above disclosure, the active material may have at least one of a silicon clathrate II type crystal phase, a silicon clathrate I type crystal phase, and a diamond type Si crystal phase.

[0015] In the above disclosure, the active material may have voids inside the primary particles.

[0016] The present disclosure also provides an all-solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein the negative electrode layer contains the above-mentioned active material and a solid electrolyte.

[0017] According to the present disclosure, by using the above-mentioned active material, it is possible to obtain an all-solid-state battery capable of suppressing the volume change of the negative electrode layer during charging and discharging.

[0018] The present disclosure also provides a method for producing the above-mentioned active material, the method including a synthesis step of synthesizing a first precursor, a washing step of washing the first precursor with an organic solvent or an acid having a relative dielectric constant of 5 or more to obtain a second precursor, and a drying step of drying the second precursor by heat to obtain the active material.

[0019] According to the present disclosure, the first precursor can be washed with an organic solvent or acid having a high relative dielectric constant, and then dried to obtain an active material capable of suppressing the volume change of the electrode layer during charge and discharge.

[0020] In the above disclosure, the organic solvent may be a ketone.

[0021] In the above disclosure, the synthesis process may include an alloying process for alloying an intermediate having at least one of a silicon clathrate II type crystal phase, a silicon clathrate I type crystal phase, and a diamond type Si crystal phase with a Li-based material to obtain an alloy compound, and a Li removal process for removing Li from the alloy compound and forming voids inside the primary particles.

[0022] In the above disclosure, the Li removal process may use ethanol to remove the Li from the alloy compound. Effect of the Invention

[0023] The present disclosure has an effect of providing an active material capable of suppressing the volume change of an electrode layer during charging and discharging. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is a schematic perspective view illustrating a crystalline phase of Si. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Diagram 3] 1 is a flowchart illustrating a method for producing an active material in the present disclosure. [Figure 4] 1 is a flow chart illustrating a method for synthesizing a first precursor in accordance with the present disclosure. [Diagram 5] 1 shows the results of IR measurement of the active materials obtained in Examples 1 and 2 and Comparative Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The active material, the all-solid-state battery, and the method for producing the active material according to the present disclosure will be described in detail below.

[0026] A. Active material The active material in the present disclosure is an active material for use in an all-solid-state battery, which contains at least Si and has an infrared spectrum of 900 cm -1 More than 950cm -1The maximum peak intensity at I 1 and 1000 cm -1 More than 1100cm -1 The maximum peak intensity at I 2 In this case, 0.55≦I 2 / I 1 ≦1.0. I 1 0.01≦I 1 Similarly, I 2 0.01≦I 2 may be satisfied.

[0027] According to this disclosure, I 2 / I 1 The value of is within a given range, and I 1 or I 2 Since the value of is also within a predetermined range, it can be an active material that can suppress the volume change of the electrode layer during charging and discharging. As described above, Si has a large theoretical capacity and is effective in increasing the energy density of a battery. On the other hand, Si has a large volume change during charging and discharging. If the volume change during charging and discharging is large, adverse effects such as a decrease in durability and a decrease in energy density due to an increase in the size of the restraining jig occur. Since the largest problem is the large volume change of the Si particles themselves, the volume change of the electrode layer is often suppressed by limiting the amount of Si particles used. However, if the amount of Si particles used is limited, it is difficult to improve the energy density.

[0028] Therefore, the present inventors have been studying the provision of voids inside the Si particles or the use of clathrate Si particles in order to reduce the volume change of the Si particles. On the other hand, the present inventors have found that the aggregation of Si particles in the electrode layer contributes to the increase in the volume change of the electrode layer. Therefore, by focusing on the functional groups and compounds present on the surface of the Si particles and controlling the surface state of the Si particles (specifically, by increasing the polarity of the surface of the Si particles), it has been found that the aggregation of the Si particles can be suppressed and the volume change of the electrode layer can be reduced. It is presumed that the reason why the aggregation of the Si particles can be suppressed is that by increasing the polarity of the surface of the Si particles, the affinity with the solid electrolyte, which generally has a high polarity, is improved, and the Si particles are uniformly dispersed during the preparation of the electrode layer. It is presumed that the charge and discharge reaction in the electrode layer is uniformed by uniformly dispersing the Si particles and increasing the contact area between the Si particles and the solid electrolyte, and as a result, the volume change of the electrode layer can be suppressed.

[0029] The active material in the present disclosure has an infrared spectrum (IR spectrum) of I 2 / I 1 is within the specified range. I 1 is 900cm -1 More than 950cm -1 The maximum peak intensity in the following region is usually Si-R (R is CH 3 The peak at 850 cm is derived from hydrophobic functional groups such as benzene, benzene, and benzene. -1 More than 880cm -1 In the following range, CO 3 2- If CO 3 2- Even if the peak of I shifts to the higher wavenumber side, 1 CO 3 2- This does not apply to the intensity of the large peaks due to I 1 is 850cm -1 More than 950cm -1 It may be the intensity of the peak derived from the following Si-R.

[0030] I 2 is 1000cm -1 More than 1100cm -1 This is the maximum peak intensity at or below 1000 cm, which is usually a peak derived from Si-O-Si present on the surface of the active material. Note that the peak derived from Si-O-Si is usually a broad peak, so there is a possibility that a clear peak will not be confirmed. In such a case, -1 More than 1100cm -1 The maximum peak intensity below 1000cm -1 More than 1100cm -1 It can be treated as the maximum intensity below.

[0031] In this disclosure, I 2 / I 1 The value of I is usually 0.55 or more, may be 0.60 or more, or may be 0.65 or more. 2 / I 1 The value of I is usually 1.0 or less, and may be 0.95 or less. 1 is usually 0.01 or more, may be 0.02 or more, or may be 0.03 or more. 1 is, for example, 0.08 or less, and may be 0.06 or less. 2 is usually 0.01 or more, may be 0.02 or more, or may be 0.03 or more. 2 is, for example, 0.08 or less, and may be 0.06 or less. Infrared spectrum (IR spectrum) in the present disclosure is a spectrum obtained by the ATR method (attenuated total reflection method). In addition, the intensity in the IR spectrum means absorbance.

[0032] The active material in the present disclosure preferably has at least one of a silicon clathrate II type crystal phase, a silicon clathrate I type crystal phase, and a diamond type Si crystal phase. The active material preferably has any of the above crystal phases as a main phase. "Having as a main phase" means that the peak belonging to the above crystal phase is the peak with the largest diffraction intensity among the peaks observed in X-ray diffraction measurement.

[0033] The active material in the present disclosure may have a silicon clathrate II crystal phase. As shown in FIG. 1(a), in the silicon clathrate II crystal phase, a polyhedron (cage) including a pentagon or hexagon is formed by a plurality of Si elements. This polyhedron has a space inside that can contain metal ions such as Li ions. By inserting metal ions into this space, the volume change due to charging and discharging can be suppressed. In particular, in an all-solid-state battery, it is generally necessary to apply a high confining pressure in order to suppress the volume change due to charging and discharging, but by using the active material in the present disclosure, the confining pressure can be reduced, and as a result, the size of the confining jig can be suppressed.

[0034] The silicon clathrate II crystal phase usually belongs to the space group (Fd-3m). The silicon clathrate II crystal phase has typical peaks at 2θ=20.09°, 21.00°, 26.51°, 31.72°, 36.26°, and 53.01° in X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°, respectively.

[0035] In the crystal phase of silicon clathrate type II, the peak at 2θ=20.09°±0.50° is defined as peak A, and the peak at 2θ=31.72°±0.50° is defined as peak B. The intensity of peak A is defined as I A and the intensity of peak B is I B On the other hand, the maximum intensity at 2θ = 22° to 23° is I MThe range of 2θ=22° to 23° can be used as a reference because it is within the range in which no peaks of the crystal phase related to Si usually appear.

[0036] I A / I M The value of I is preferably greater than 1. A / I M When the value is 1 or less, it can be determined that the silicon clathrate II type crystal phase is not substantially formed. A / I M The value of I is, for example, 2 or more, may be 5 or more, or may be 7 or more. A / I M There is no particular upper limit to the value of I A / I M can reach values ​​of 1000 or more.

[0037] I B / I M The value of I is preferably greater than 1. B / I M When the value is 1 or less, it can be determined that the silicon clathrate II type crystal phase is not substantially formed. B / I M The value of is, for example, 2 or more, and may be 5 or more. B / I M There is no particular upper limit to the value of I B / I M can reach values ​​of 1000 or more.

[0038] The active material in the present disclosure has a silicon clathrate II type crystalline phase, and may not have a diamond-type Si crystalline phase, which will be described later. The fact that it "does not have a crystalline phase" can be confirmed by the fact that the peak of the crystalline phase is not confirmed in an X-ray diffraction measurement. In addition, the active material in the present disclosure has a silicon clathrate II type crystalline phase, and may not have a silicon clathrate I type crystalline phase, which will be described later.

[0039] The active material in the present disclosure may have a crystal phase of silicon clathrate type I. As shown in Fig. 1(b), in the crystal phase of silicon clathrate type I, similar to silicon clathrate type II, multiple Si elements form polyhedrons (cages) including pentagons or hexagons, and thus the volume change due to charging and discharging can be suppressed.

[0040] The silicon clathrate I type crystal phase usually belongs to the space group (Pm-3n). The silicon clathrate I type crystal phase has typical peaks at 2θ=19.44°, 21.32°, 30.33°, 31.60°, 32.82°, 36.29°, 52.39°, and 55.49° in X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°, respectively.

[0041] The active material in the present disclosure may have a diamond-type Si crystal phase. As shown in FIG. 1(c), normal Si has a diamond-type crystal phase. In the diamond-type Si crystal phase, a tetrahedron is formed by a plurality of Si elements. The tetrahedron does not have a space inside that can contain metal ions such as Li ions, so it is difficult to suppress the volume change caused by charging and discharging. On the other hand, it has an advantage that the manufacturing cost is lower than that of silicon clathrate.

[0042] The diamond-type Si crystal phase has typical peaks at 2θ=28.44°, 47.31°, 56.10°, 69.17°, and 76.37° in X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°, respectively.

[0043] The active material in the present disclosure contains at least Si. The active material contains at least Si, and may contain only Si, or may further contain other elements. Examples of other elements include metal elements such as Li and Na. Elements contained in functional groups or compounds present on the surface of the active material (e.g., O, C, H) are not taken into consideration. The active material may or may not have a SiO skeleton. For example, when the active material has a silicon clathrate II type crystal phase, its composition may contain Na x S 136 It is preferable that the composition is represented by (0≦x≦20). x may be 0 or may be greater than 0. On the other hand, x may be 10 or less, or 5 or less. The composition of the active material can be determined by, for example, EDX, XRD, XRF, ICP, or atomic absorption spectrometry.

[0044] The shape of the active material in the present disclosure may be, for example, particulate. The active material may be primary particles, or may be secondary particles formed by agglomeration of primary particles. The average particle size of the primary particles is, for example, 50 nm or more, 100 nm or more, or 150 nm or more. On the other hand, the average particle size of the primary particles is, for example, 3000 nm or less, 1500 nm or less, or 1000 nm or less. In addition, the average particle size of the secondary particles is, for example, 1 μm or more, 2 μm or more, or 5 μm or more. On the other hand, the average particle size of the secondary particles is, for example, 60 μm or less, or 40 μm or less. The average particle size can be determined, for example, by observation using a SEM. The number of samples is preferably large, for example, 20 or more, 50 or more, or 100 or more.

[0045] The active material in the present disclosure preferably has voids inside the primary particles. This is because the volume change during charging and discharging can be made smaller. In particular, the active material preferably has many microvoids with a pore diameter of 100 nm or less. This is because the collapse of the voids due to pressing can be suppressed. The void volume of the pores with a pore diameter of 100 nm or less is, for example, 0.05 cc / g or more, may be 0.07 cc / g or more, or may be 0.10 cc / g or more. On the other hand, the void volume is, for example, 0.15 cc / g or less. The void volume can be determined, for example, by mercury porosimeter measurement, BET measurement, gas adsorption method, 3D-SEM, and 3D-TEM.

[0046] When the active material in the present disclosure has voids inside the primary particles, the porosity is, for example, 4% or more, and may be 10% or more. The porosity is, for example, 40% or less, and may be 20% or less. The porosity can be determined, for example, by the following procedure. First, a cross section of an electrode layer containing an active material is taken by ion milling. The cross section is then observed with a SEM (scanning electron microscope) to obtain a photograph of the particles. From the obtained photograph, silicon parts and void parts are clearly distinguished using image analysis software, and the image is binarized. The areas of the silicon parts and void parts are determined, and the porosity (%) is calculated from the following formula. Porosity (%) = 100 × (area of ​​void part) / ((area of ​​silicon part) + (area of ​​void part))

[0047] Specific image analysis and porosity calculation can be performed as follows. For example, Fiji ImageJ bundled with Java 1.8.0_172 (hereinafter, Fiji) is used as image analysis software. A secondary electron image and a backscattered electron image of the same field of view are combined to create an RGB color image. Then, in order to remove noise for each pixel, the obtained RGB image is blurred using the Fiji function "Median (filter size = 2)". Next, using the Fiji function "Weka Machine Learning", a person manually designates multiple arbitrary areas in the image from which the noise has been removed as silicon parts or void parts, respectively, to create training data that distinguishes between silicon parts and void parts. Then, based on the created training data, a machine distinguishes between silicon parts and void parts within Fiji, and the area ratio of the silicon parts and void parts is calculated.

[0048] For RGB color imaging, since both the secondary electron image and the backscattered electron image are expressed in grayscale, for example, the brightness x of each pixel in the secondary electron image is assigned to the Red value, and the brightness y of the backscattered electron image is similarly assigned to the Green value. This results in an RGB image where, for example, each pixel is represented as R=x, G=y, B=(x+y) / 2.

[0049] Detailed conditions for the above "Weka Machine Learning" are shown below. As training features (numerical image features that the machine focuses on when creating training data in machine learning), select Gaussian blur, Hessian, Membrane projections, Mean, Maximum, Anisotropic diffusion, Sobel filter, Difference of Gaussians, Variance, Minimum, and Median. As for other parameters, set Membrane thickness to 3, Membrane patch size to 19, Minimum sigma to 1.0, and Maximum sigma to 16.0.

[0050] The active material in the present disclosure is usually used in an all-solid-state battery. The active material in the present disclosure may be either an anode active material or a cathode active material, with the former being preferred. The present disclosure can also provide an electrode layer (anode layer or cathode layer) having the above-mentioned active material, and an all-solid-state battery having the electrode layer. Examples of methods for producing the active material include the methods described in "C. Method for producing active material" below.

[0051] B. All-solid-state battery Fig. 2 is a schematic cross-sectional view illustrating an example of an all-solid-state battery in the present disclosure. The all-solid-state battery 10 shown in Fig. 2 has a positive electrode layer 1, a negative electrode layer 2, a solid electrolyte layer 3 formed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode current collector 4 that collects current from the positive electrode layer 1, and a negative electrode current collector 5 that collects current from the negative electrode layer 2. In the present disclosure, the negative electrode layer 2 contains the above-mentioned active material and a solid electrolyte.

[0052] According to the present disclosure, by using the above-mentioned active material, it is possible to obtain an all-solid-state battery capable of suppressing the volume change of the negative electrode layer during charging and discharging.

[0053] 1. Negative electrode layer The negative electrode layer is a layer containing at least a negative electrode active material and a solid electrolyte, and may contain at least one of a conductive material and a binder, as necessary.

[0054] The negative electrode active material is the same as that described in "A. Active material" above, so the description here is omitted. The ratio of the negative electrode active material in the negative electrode layer is, for example, 20% by weight or more, may be 30% by weight or more, or may be 40% by weight or more. If the ratio of the negative electrode active material is too small, there is a possibility that sufficient energy density cannot be obtained. On the other hand, the ratio of the negative electrode active material is, for example, 80% by weight or less, may be 70% by weight or less, or may be 60% by weight or less. If the ratio of the negative electrode active material is too high, there is a possibility that the ionic conductivity and electronic conductivity in the negative electrode layer are relatively reduced.

[0055] The negative electrode layer may contain at least one of a solid electrolyte, a conductive material, and a binder, as necessary. Examples of the solid electrolyte include the solid electrolytes described in "3. Solid Electrolyte Layer" below. Examples of the conductive material include carbon materials, metal particles, and conductive polymers. Examples of the carbon material include particulate carbon materials such as acetylene black (AB) and Ketjen black (KB), and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNT), and carbon nanofibers (CNF). Examples of the binder include rubber-based binders and fluoride-based binders.

[0056] The thickness of the negative electrode layer is, for example, 0.1 μm or more and 1000 μm or less. The negative electrode layer in the present disclosure is generally used in an all-solid-state battery.

[0057] 2. Positive electrode layer The positive electrode layer is a layer containing at least a positive electrode active material, and may contain at least one of a solid electrolyte, a conductive material, and a binder, as necessary.

[0058] The positive electrode active material may be, for example, an oxide active material. For example, LiCoO 2 , LiMnO 2 , LiNiO 2 , LiVO 2 , LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 Rock salt layered active materials such as LiMn 2 O 4 , Li 4 Ti 5 O 12 , Li(Ni 0.5 Mn 1.5 )O 4 Spinel-type active materials such as LiFePO 4 , LiMnPO 4 , LiNiPO 4 , LiCoPO 4 Examples of the olivine type active material include those mentioned above.

[0059] A coating layer containing a Li-ion conductive oxide may be formed on the surface of the oxide active material. This is because it is possible to suppress the reaction between the oxide active material and a solid electrolyte (particularly a sulfide solid electrolyte). Examples of Li-ion conductive oxides include LiNbO 3 The thickness of the coating layer is, for example, 1 nm or more and 30 nm or less. In addition, the positive electrode active material is, for example, Li 2 S can also be used.

[0060] The solid electrolyte, conductive material, and binder used in the positive electrode layer are the same as those described in "1. Negative electrode layer" above, so the description here is omitted. The thickness of the positive electrode layer is, for example, 0.1 μm or more and 1000 μm or less.

[0061] 3.Solid electrolyte layer The solid electrolyte layer is a layer formed between the positive electrode layer and the negative electrode layer, and contains at least a solid electrolyte.

[0062] Examples of the solid electrolyte include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes. Examples of the sulfide solid electrolyte include solid electrolytes containing Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S element. The sulfide solid electrolyte may further contain at least one of O element and halogen element. Examples of the halogen element include F element, Cl element, Br element, and I element. The sulfide solid electrolyte may be glass (amorphous) or glass ceramics. Examples of the sulfide solid electrolyte include Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S element. The sulfide solid electrolyte may further contain at least one of O element and halogen element. Examples of the halogen element include F element, Cl element, Br element, and I element. The sulfide solid electrolyte may be glass (amorphous) or glass ceramics. 2 SP 2 S 5 , LiI-Li 2 SP 2 S 5 , LiI-LiBr-Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2S-GeS 2 , Li 2 SP 2 S 5 -GeS 2 Examples include:

[0063] The thickness of the solid electrolyte layer is, for example, not less than 0.1 μm and not more than 1000 μm.

[0064] 4.Other configurations The all-solid-state battery of the present disclosure preferably has a positive electrode current collector that collects the positive electrode layer and a negative electrode current collector that collects the negative electrode layer. Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. On the other hand, examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon.

[0065] The all-solid-state battery of the present disclosure may further include a restraining tool that applies a restraining pressure to the positive electrode layer, the solid electrolyte layer, and the negative electrode layer along the thickness direction. By using the restraining tool, good ion conduction paths and electron conduction paths can be formed. The restraining pressure is, for example, 0.1 MPa or more, may be 1 MPa or more, or may be 5 MPa or more. On the other hand, the restraining pressure is, for example, 100 MPa or less, may be 50 MPa or less, or may be 20 MPa or less.

[0066] 5.All-solid-state battery The type of all-solid-state battery in the present disclosure is not particularly limited, but is typically a lithium-ion battery. The all-solid-state battery in the present disclosure may be a primary battery or a secondary battery, but is preferably a secondary battery, because it can be repeatedly charged and discharged and is useful, for example, as an in-vehicle battery.

[0067] The all-solid-state battery in the present disclosure may be a single cell or a stacked battery. The stacked battery may be a monopolar stacked battery (a parallel-connected stacked battery) or a bipolar stacked battery (a series-connected stacked battery). The shape of the all-solid-state battery may be, for example, a coin type, a laminate type, a cylindrical type, or a square type.

[0068] C. Method of manufacturing active material FIG. 3 is a flow chart illustrating a method for producing an active material in the present disclosure. In the production method shown in FIG. 3, a first precursor is first synthesized. Next, the first precursor is washed with an organic solvent or acid having a relative dielectric constant of 5 or more to obtain a second precursor. Next, the second precursor is dried by heat to obtain a target active material. FIG. 4 is a flow chart illustrating a method for synthesizing a first precursor in the present disclosure. In FIG. 4, a Zintl compound containing Na and Si and having at least a Zintl phase is produced, and Na is removed from the Zintl compound to obtain an intermediate having a silicon clathrate II type crystal phase. Next, the intermediate and a Li-based material are alloyed at a predetermined ratio to obtain an alloy compound (alloying process). Next, Li is removed from the alloy compound to form voids inside the primary particles (Li removal process). As a result, a first precursor having a silicon clathrate II type crystal phase is obtained.

[0069] According to the present disclosure, the first precursor is washed with an organic solvent or acid having a high relative dielectric constant, and then dried to obtain an active material capable of suppressing the volume change of the negative electrode layer during charging and discharging. 2 H 5 OH (compounds with OH group), CH 3 COONa, C.H. 3 When COOLi is present, the surface of the active material is coated with Si-R (R is CH 3 It is presumed that the surface polarity of the active material is reduced by the formation of hydrophobic functional groups such as Si-R. 1 In contrast, in the present disclosure, the surface of the active material is treated with an organic solvent or acid having a high relative dielectric constant, thereby 2 H 5 OH and other atoms can be removed. Therefore, even if a drying process is performed, the ratio of Si-R can be reduced. As a result, the ratio of highly polar Si-O-Si can be increased, and aggregation of the active material can be suppressed during the preparation of the electrode layer.

[0070] 1.Synthesis process The synthesis step in the present disclosure is a step of synthesizing a first precursor. The first precursor corresponds to the active material before the washing step. The first precursor contains at least Si, and may contain only Si, or may further contain other elements. The other elements are the same as those described in "A. Active material" above. In addition, it is preferable that the first precursor has at least one of a silicon clathrate II type crystal phase, a silicon clathrate I type crystal phase, and a diamond type Si crystal phase. In addition, it is preferable that the first precursor has any of the above crystal phases as a main phase.

[0071] The synthesis method of the first precursor is not particularly limited, and may be, for example, a method including an alloying process for alloying an intermediate having at least one of a silicon clathrate II type crystal phase, a silicon clathrate I type crystal phase, and a diamond type Si crystal phase with a Li-based material to obtain an alloy compound, and a Li removal process for removing Li from the alloy compound to form voids inside the primary particles.

[0072] (1) Intermediates The intermediate preferably has at least one of a silicon clathrate II type crystal phase, a silicon clathrate I type crystal phase, and a diamond type Si crystal phase. The first precursor preferably has any of the above crystal phases as a main phase. For example, commercially available Si particles can be used as an intermediate having a diamond type Si crystal phase. On the other hand, an intermediate having a silicon clathrate II type crystal phase or a silicon clathrate I type crystal phase can be obtained by, for example, a method of removing Na from a Zintl compound containing Na and Si and having at least a Zintl phase. By adjusting the conditions for removing Na, the ratio of the silicon clathrate II type crystal phase and the silicon clathrate I type crystal phase can be adjusted. Hereinafter, a method for preparing an intermediate having a silicon clathrate II type crystal phase or a silicon clathrate I type crystal phase will be described.

[0073] (i) Zintle Production The Zintl compound has a Zintl phase. The Zintl phase has typical peaks at 2θ=16.10°, 16.56°, 17.64°, 20.16°, 27.96°, 33.60°, 35.68°, 40.22°, and 41.14° in an X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, or may vary within a range of ±0.30°. The Zintl compound preferably has a Zintl phase as a main phase. The Zintl compound may or may not have a silicon clathrate I type crystal phase. The Zintl compound may or may not have a silicon clathrate II type crystal phase.

[0074] The composition of the Zintle compound is not particularly limited, but may be Na z S 136 It is preferable that the composition is represented by the formula (121≦z≦151). z may be 126 or more, or may be 131 or more. On the other hand, z may be 141 or less.

[0075] The Zintl compound can be obtained, for example, by subjecting a raw material mixture containing Na (single element) and Si (single element) to heat treatment. The ratio of Na (single element) and Si (single element) is not particularly limited, but Na (single element) may be, for example, 0.8 molar parts or more, or 1 molar part or more, per 1 molar part of Si (single element). On the other hand, Na (single element) may be, for example, 1.5 molar parts or less, or 1.3 molar parts or less, per 1 molar part of Si (single element).

[0076] The heat treatment temperature is, for example, 500° C. or higher and 1000° C. or lower. The heat treatment time is, for example, 1 hour or higher and 50 hours or lower. In particular, it is preferable to perform the heat treatment under the conditions of about 700° C. (for example, 650° C. or higher and 750° C. or lower) and about 20 hours (for example, 15 hours or higher and 25 hours or lower).

[0077] (ii) Sodium removal A method for removing Na from the Zintl compound includes, for example, heat treatment. The heat treatment temperature is, for example, 280° C. or higher, and may be 300° C. or higher. Meanwhile, the heat treatment temperature is, for example, 500° C. or lower. The heat treatment time is, for example, 1 hour or more and 50 hours or less. The heat treatment may be performed in a normal pressure atmosphere or a reduced pressure atmosphere. In the latter case, the pressure during the heat treatment is, for example, 10 Pa or lower, may be 1 Pa or lower, or may be 0.1 Pa or lower. The heat treatment may also be performed in an inert atmosphere such as an Ar atmosphere.

[0078] (iii) Intermediate The composition of the intermediate obtained by the above-mentioned method is not particularly limited, but may be Na y S 136 It is preferable that the formula is expressed as (0≦y≦24). y may be 0 or may be greater than 0. On the other hand, y may be 20 or less, or may be 10 or less.

[0079] (2) Alloying treatment The alloying treatment in the present disclosure is a treatment in which the intermediate is alloyed with a Li-based material to obtain an alloy compound.

[0080] The Li-based material is not particularly limited as long as it is a material that can be alloyed with the intermediate, and may be Li alone or a Li alloy. The Li alloy is preferably an alloy mainly composed of Li. This is because it is easy to alloy with the intermediate. Examples of methods for alloying the intermediate and the Li-based material include a method of mixing the two and a method of heat-treating the two.

[0081] In the alloying step, it is preferable to alloy the intermediate and the Li-based material with a molar ratio (Li / Si) of Li contained in the Li-based material to Si contained in the intermediate within a predetermined range. Li / Si is, for example, 0.5 or more, and may be 0.75 or more, or may be 1 or more. If Li / Si is too small, there is a possibility that voids will not be formed inside the primary particles. On the other hand, Li / Si is, for example, 3 or less, and may be 2.5 or less, or may be 2 or less. If Li / Si is too large, there is a possibility that the desired crystal phase cannot be maintained. Since the crystallinity of Si tends to decrease when alloyed with Li, it is preferable to control Li / Si.

[0082] (3) Lithium removal treatment The Li removal process in the present disclosure is a process of removing Li from the alloy compound and forming voids inside the primary particles. By removing the Li (highly dispersed Li) contained in the alloy compound, nano-sized (nano-order) voids can be formed.

[0083] As a method for removing Li from an alloy compound, for example, a method of reacting a Li extractant with the alloy compound can be mentioned. The Li extractant is, for example, a liquid. Examples of the Li extractant include primary alcohols such as methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, and 1-hexanol, secondary alcohols such as 2-propanol, 2-butanol, 2-pentanol, and 2-hexanol, tertiary alcohols such as tert-butyl alcohol, phenols such as phenol, glycols such as 1,2-ethanediol and 1,3-butanediol, glycol ethers such as propylene glycol monomethyl ether and ethylene glycol monomethyl ether, pyranoses such as bD-glucopyranose, furanoses such as erythrofuranose, and polysaccharides such as glucose and fructose. The Li extractant is preferably at least one of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, and 1-hexanol. In particular, the Li extractant preferably contains at least ethanol. In addition, as the Li extractant, for example, an acid such as acetic acid, formic acid, propionic acid, or oxalic acid may be used. In the present disclosure, two or more kinds of Li extractants may be used. In this case, two or more kinds of Li extractants may be mixed and used, or may be used separately (two or more stages of treatment may be performed to remove Li).

[0084] The Li extractant preferably has a low moisture content. If the moisture content is too high, the alloy compound may deteriorate. The moisture content of the Li extractant is, for example, 100 ppm or less, and may be 10 ppm or less. The weight ratio of the Li extractant to the alloy compound is, for example, 5 or more, may be 10 or more, or may be 15 or more. On the other hand, the weight ratio is, for example, 500 or less, and may be 250 or less.

[0085] The method of reacting the Li extractant with the alloy compound is not particularly limited. The Li extractant may be directly contacted with the alloy compound, or the Li extractant may be contacted with a dispersion liquid in which the alloy compound is dispersed. Examples of the dispersion medium include saturated hydrocarbons such as n-heptane, n-octane, n-decane, 2-ethylhexane, and cyclohexane, unsaturated hydrocarbons such as hexene and heptene, aromatic hydrocarbons such as 1,3,5-trimethylbenzene, toluene, xylene, ethylbenzene, propylbenzene, cumene, 1,2,4-trimethylbenzene, and 1,2,3-trimethylbenzene, and ethers such as n-butyl ether, n-hexyl ether, isoamyl ether, diphenyl ether, methyl phenyl ether, and cyclopentyl methyl ether. The relative dielectric constant of the dispersion medium is, for example, 3.08 or less, and may be 3.00 or less. On the other hand, the relative dielectric constant of the dispersion medium is, for example, 1.50 or more, and may be 1.70 or more. The relative dielectric constant can be measured, for example, by the method described in JIS C 2565 (such as the cavity resonator method).

[0086] 2. Cleaning process The washing step in the present disclosure is a step of washing the first precursor with an organic solvent or acid having a relative dielectric constant of 5 or more to obtain a second precursor. The second precursor corresponds to the active material after the washing step and before the drying step. In addition, the second precursor and the first precursor usually have the same crystal phase.

[0087] The relative dielectric constant (25°C) of the organic solvent or acid is usually 5 or more, may be 10 or more, or may be 15 or more. Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone, and diethyl ketone, alcohols such as ethanol, methanol, and propanol, esters such as methyl acetate, ethyl acetate, butyl acetate, and butyl butyrate, and ethers such as diethyl ether and dibutyl ether. Aromatic hydrocarbons may also be used as the organic solvent. On the other hand, examples of the acid include inorganic acids such as hydrochloric acid, sulfuric acid, and nitric acid.

[0088] The method of washing the first precursor with an organic solvent includes, for example, immersing the first precursor in an organic solvent. In this case, ultrasonic treatment may be performed. Alternatively, the first precursor may be washed by spraying the organic solvent onto it. The washing time is not particularly limited, but is, for example, 10 minutes or more and 10 hours or less. The second precursor has a peak at 2800 cm in the infrared spectrum. -1 More than 3500cm -1 The following peaks derived from -OH may be present.

[0089] 3.Drying process The drying step in the present disclosure is a step of drying the second precursor by heat to obtain the active material. The drying step is a step of removing an organic solvent or an acid from the second precursor. For example, when the second precursor contains Na, Na may or may not be removed from the second precursor in the drying step.

[0090] The drying temperature is, for example, 280° C. or higher, and may be 300° C. or higher. On the other hand, the drying temperature is, for example, 500° C. or lower. The drying time is, for example, 1 hour or more and 50 hours or less. The drying may be performed in a normal pressure atmosphere or a reduced pressure atmosphere. In the latter case, the pressure during drying is, for example, 10 Pa or less, 1 Pa or less, or 0.1 Pa or less. The drying may also be performed in an inert atmosphere such as an Ar atmosphere. In addition, an example of a drying method is a method using a firing furnace.

[0091] 4.Active material The active material obtained by the above steps is the same as that described above in "A. Active material," and therefore will not be described here.

[0092] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0093] [Example 1] (Synthesis of active materials) Si particles and Na particles were mixed in a molar ratio of 1:1, put into a crucible, sealed under an Ar atmosphere, and heated at 700°C to synthesize NaSi (Zintle compound). After that, Na was removed by heating at 340°C under vacuum (about 1 Pa) to obtain an intermediate. The obtained intermediate and Li metal were weighed in a molar ratio of Li / Si=1 and mixed in a mortar in an Ar atmosphere to obtain an alloy compound. The obtained alloy compound was reacted with ethanol in an Ar atmosphere to form voids inside the primary particles, and a first precursor was obtained. The ratio of the alloy compound and ethanol was alloy compound:ethanol=12:400 by weight.

[0094] Next, the obtained first precursor was washed. Specifically, it was immersed in acetone and ultrasonically treated for 30 minutes using an ultrasonic device (US-3KS manufactured by SND) to obtain a second precursor. After that, it was dried in a baking furnace at 430°C for 6 hours to obtain an active material.

[0095] (Preparation of negative electrode) The obtained active material, sulfide solid electrolyte (Li 2 SP 2 S 5 A butyl butyrate solution containing 5% by weight of PVDF-based binder, butyl butyrate, and butyl butyrate were added and stirred for 30 seconds with an ultrasonic dispersing device (UH-50, manufactured by SMT). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied to a negative electrode current collector (Cu foil, manufactured by UACJ) by the blade method using an applicator, and dried for 30 minutes on a hot plate at 100°C. This resulted in a negative electrode having a negative electrode current collector and a negative electrode layer.

[0096] (Preparation of positive electrode) The positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2, average particle size 6 μm), sulfide solid electrolyte (Li 2 SP 2 S 5 A butyl butyrate solution containing 5% by weight of PVDF-based binder, butyl butyrate, and butyl butyrate were added and stirred for 30 seconds with an ultrasonic dispersion device (UH-50, manufactured by SMT). Next, the container was shaken for 3 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied to a positive electrode collector (Al foil, manufactured by Showa Denko) by the blade method using an applicator, and dried for 30 minutes on a hot plate at 100°C. This resulted in a positive electrode having a positive electrode collector and a positive electrode layer. The area of ​​the positive electrode was smaller than that of the negative electrode.

[0097] (Preparation of solid electrolyte layer) A polypropylene container is filled with a sulfide solid electrolyte (Li 2 SP 2 S 5 A heptane solution containing 5% by weight of a butylene rubber-based binder, a 5% by weight tungsten-based glass ceramic, and heptane were added, and the mixture was stirred for 30 seconds with an ultrasonic dispersing device (UH-50, manufactured by SMT). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied onto a release sheet (Al foil) by the blade method using an applicator, and dried on a hot plate at 100°C for 30 minutes. This resulted in a transfer member having a release sheet and a solid electrolyte layer.

[0098] (Production of all-solid-state batteries) A solid electrolyte layer for bonding was placed on the positive electrode layer of the positive electrode, and the resulting mixture was set in a roll press machine and pressed at 20 kN / cm (approximately 710 MPa) and 165° C. This produced a first laminate.

[0099] Next, the negative electrode was set in a roll press machine and pressed at 20 kN / cm (about 630 MPa) and 25°C. Then, a solid electrolyte layer for bonding and a transfer member were arranged in order from the negative electrode layer side. At this time, the solid electrolyte layer for bonding and the solid electrolyte layer on the transfer member were arranged so as to face each other. The obtained laminate was set in a flat uniaxial press machine and temporarily pressed at 100 MPa and 25°C for 10 seconds. Then, the release sheet was peeled off from the solid electrolyte layer. This resulted in a second laminate.

[0100] Next, the solid electrolyte layer for bonding in the first laminate and the solid electrolyte layer in the second laminate were arranged to face each other, and then set in a flat uniaxial press and pressed at 200 MPa and 135° C. for 1 minute to obtain an all-solid-state battery.

[0101] [Example 2] Except for changing the ratio of the alloy compound and ethanol to alloy compound:ethanol=1:150 by weight, an active material was obtained in the same manner as in Example 1. An all-solid-state battery was obtained in the same manner as in Example 1 using the obtained active material.

[0102] [Comparative Examples 1 and 2] Except for not washing the first precursor, an active material was obtained in the same manner as in Examples 1 and 2. An all-solid-state battery was obtained in the same manner as in Example 1 using the obtained active material.

[0103] [Comparative Example 3] An all-solid-state battery was obtained in the same manner as in Example 1, except that commercially available Si particles (diamond-type Si particles) were used.

[0104] [evaluation] (IR measurement) Infrared spectroscopy (IR) was performed on the active materials obtained in Examples 1 and 2 and Comparative Examples 1 to 3. The IR measurements were performed using a single reflection ATR method (ATR accessory: Thunderdome manufactured by SpectraTech), a DTGS detector, and a wavenumber resolution of 4 cm. -1 The test was performed under the condition of 128 integration times. The results are shown in Table 1 and Figure 5.

[0105] (Measurement of increase in confining pressure) The all-solid-state batteries obtained in Examples 1 and 2 and Comparative Examples 1 to 3 were charged, and the increase in the confining pressure was measured. The test conditions were confining pressure (constant dimension) 5 MPa, charging 0.1 C, and cut voltage 4.55 V, and the confining pressure at 4.55 V was measured to determine the increase in the confining pressure from the state before charging. The results are shown in Table 1. The results of the increase in the confining pressure in Table 1 are relative values ​​when the result of Comparative Example 1 is set to 100.

[0106] (XRD measurement) X-ray diffraction (XRD) measurements using CuKα radiation were performed on the active materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2. As a result, it was confirmed that the active materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2 had a silicon clathrate II type crystal phase as the main phase among the crystal phases.

[0107] In addition, the intensity of peak A located near 2θ=20.09° in the silicon clathrate II crystal phase is I A The intensity of peak B located near 2θ = 31.72° is I B The maximum intensity at 2θ = 22° to 23° was defined as I M And, I A / I M and I B / I M The results are shown in Table 1.

[0108] (Measurement of void volume) The void volume (void volume of pores with a pore diameter of 100 nm or less) of the active materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2 was determined. A mercury porosimeter was used to measure the void volume. The measurement was performed in the range of 40 Å to 4,000,000 Å using a Pore Master 60-GT (Quanta Chrome Co.). The analysis was performed using the Washburn method. The results are shown in Table 1.

[0109] (SEM measurement) SEM-EDX (scanning electron microscope-energy dispersive X-ray spectroscopy) measurement was performed on the active materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2. As a result, it was confirmed that nano-sized voids were formed inside the primary particles of the active materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2.

[0110] [Table 1]

[0111] As shown in Table 1 and FIG. 5, in Examples 1 and 2, compared with Comparative Examples 1 and 2, I 2 / I 1 It was confirmed that the value of I was large and the increase in the confining pressure was significantly small. Specifically, in Examples 1 and 2, the increase in the confining pressure was reduced by 70% or more compared to Comparative Example 1. This is presumably because the high polarity of the surface of the Si particles results in good affinity with solid electrolytes, which generally have high polarity, and the Si particles are uniformly dispersed during the preparation of the negative electrode layer. In addition, it is presumed that the uniform dispersion of the Si particles increases the contact area between the Si particles and the solid electrolyte, which makes the charge and discharge reaction in the negative electrode layer uniform, and as a result, the volume change of the negative electrode can be suppressed. On the other hand, in Comparative Example 3, I 2 / I 1 Although the value of I 2 and I 1 The value of was small and the increase in confining pressure was large.

[0112] In addition, in Examples 1 and 2 and Comparative Examples 1 and 2, I A / I M and I B / I M Both values ​​were greater than 1, confirming that a silicon clathrate II type crystal phase was formed. B / I M The value of was 1 or less, and no silicon clathrate II crystal phase was formed. [Explanation of symbols]

[0113] 1 ... Positive electrode layer 2 … Negative electrode layer 3 … Solid electrolyte layer 4 … Positive electrode current collector 5 … Negative electrode current collector 10 … All-solid-state battery

Claims

1. An active material for use in an all-solid-state battery, Contains at least Si, In the infrared spectrum, -1 More than 950cm -1 The maximum peak intensity in the following is I 1 and 1000 cm -1 More than 1100cm -1 The maximum peak intensity in the following is I 2 In this case, I 1 and I 2 However, 0.55≦I 2 / I 1 ≦1.0 and 0.01≦I 1 Active materials that satisfy the above requirements.

2. I 1 However, 0.02≦I 1 2. The active material according to claim 1, wherein the active material satisfies ≦0.

08.

3. An active material for use in an all-solid-state battery, Contains at least Si, In the infrared spectrum, -1 More than 950cm -1 The maximum peak intensity in the following is I 1 and 1000 cm -1 More than 1100cm -1 The maximum peak intensity in the following is I 2 In this case, I 1 and I 2 However, 0.55≦I 2 / I 1 ≦1.0 and 0.01≦I 2 Active materials that satisfy the above requirements.

4. I 2 However, 0.02≦I 2 The active material according to claim 3 , wherein the active material satisfies ≦0.

08.

5. 5. The active material according to claim 1, wherein the active material has at least one of a silicon clathrate II type crystal phase, a silicon clathrate I type crystal phase, and a diamond type Si crystal phase.

6. The active material according to claim 1 , wherein the active material has voids inside the primary particles.

7. An all-solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, 7. An all-solid-state battery, wherein the negative electrode layer contains the active material according to claim 1 and a solid electrolyte.

8. A method for producing an active material according to any one of claims 1 to 6, comprising the steps of: a synthesis step of synthesizing a first precursor; a washing step of washing the first precursor with an organic solvent or an acid having a relative dielectric constant of 5 or more to obtain a second precursor; a drying step of drying the second precursor by heat to obtain the active material; A method for producing an active material having the above structure.

9. The method for producing an active material according to claim 8 , wherein the organic solvent is a ketone.

10. The synthesis step comprises: an alloying treatment for alloying an intermediate having at least one of a silicon clathrate II type crystal phase, a silicon clathrate I type crystal phase, and a diamond type Si crystal phase with a Li-based material to obtain an alloy compound; a Li removal treatment for removing Li from the alloy compound to form voids inside the primary particles; The method for producing an active material according to claim 8 or claim 9, comprising:

11. The method for producing an active material according to claim 10 , wherein the Li removal treatment involves removing the Li from the alloy compound using ethanol.

Citation Information

Patent Citations

  • Negative electrode active material for lithium ion secondary battery

    JP2011108635A

  • Negative electrode for sulfide all-solid battery, and sulfide all-solid battery and manufacturing method of the same

    JP2018142431A

  • Silicon-based nanoparticle-containing hydrogen polysilsesquioxane, silicone oxide structure, and manufacturing method therefor

    JP2019119638A

  • Negative electrode material and manufacturing method of the same

    JP2020017389A

  • Manufacturing method of active material, active material and battery

    JP2020064716A